Changes in Soil Physical Properties and Carbon Protection Mechanisms by Surface Application of Lime in a Tropical No‐Tillage System. Issue 1 (25th January 2018) - Carmeis Filho, Antonio C. A.; Crusciol, Carlos A. C.; Guimarães, Tiara M.; Calonego, Juliano C.; da Costa, Claudio H. M.
Abstract : Core Ideas: Liming helped avoid structural degradation. Liming effectively increased the stabilization of soil organic matter. More stable soil structure was achieved by liming. Long‐term no‐till soils often have layers that are severely affected by physical and chemical degradation. Soil acidity is associated with physical problems, such as higher bulk density, that restrict root growth and crop production, especially in tropical regions with dry seasons. Liming is the most common practice adopted to alleviate soil acidity, but limited information is available regarding the long‐term effect of lime applied superficially on soil physical attributes and the distribution of organic C in different aggregate size groups. In an Oxisol managed under a no‐tillage system for 12 yr, a trial was established with four lime rates (0, 1000, 2000, and 4000 kg ha –1 ) estimated using the base saturation method. The results showed that among the treatments, the rate calculated to increase the base saturation at 70% (2000 kg ha –1 ) provided a higher formation of water‐stable (WS) macroaggregates of >2.00 to 8.00 mm size class at 0‐ to 0.40‐m depth, and a significant decrease in the stability of the largest aggregates when the highest rate was applied. Increased values of mean weight diameter (MWD) and geometric mean diameter (GMD) were estimated with the application of rates varying from 1500 to 2500 kg ha –1 . Liming increased carbon‐protection mechanisms, resulting in an accumulation of organic C in all aggregate size classes, mainly in the >0.105 to 0.25 and >0.25 to 2.00 mm size classes. Improving the formation of WS aggregates and total organic carbon (TOC) content with liming influenced positively the total porosity, macroporosity, and soil bulk density in the deepest soil layers (0.20–0.40 and 0.40–0.60 m).